Coccolithophore assemblage distribution along a temperate to polar gradient in the West Pacific sector of the Southern Ocean (January 2005). - Malinverno, E.; Triantaphyllou, M.; Dimiza, M. (Micropaleontology, 2015)
We document surface coccolithophore species composition along a N-S transect from New Zealand to the Ross Sea, across the fronts of the Antarctic Circumpolar Current. Emiliania huxleyi is the most abundant coccolithophore species throughout, with high concentration in the northernmost samples, in the Polar Frontal Zone and at the Polar Front. Three E. huxleyi morphotypes, A, B/C and O were recognized and show different biogeographic distributions along the investigated transect. Coccolithophore distribution appears to be strongly controlled by the location of oceanographic fronts, with minor species (Calcidiscus leptoporus, Syracosphaera spp., Acanthoica quattrospina, Umbellosphaera tenuis, Corisphaera strigilis and other holococcolithophores) largely restricted to the northern Sub-Antarctic Zone, only showing minor occurrence in the southern Sub-Antarctic Zone and being very rare in the Polar Frontal Zone. Our data confirm previous findings and add new information on the biogeography of minor coccolithophore species in relation with oceanographic features. Overall, integration with previous data on the southern extent distribution of E. huxleyi showed no significant temporal shifts in the polar dynamic perspective of the species since early observations.